ASUHAN KEPERAWATAN DENGAN INTERVENSI HOLY QURAN RECITATION (HQR) TERHADAP TANDA-TANDA VITAL PASIEN PENURUNAN KESADARAN DI ICU RSUD TARAKAN - Sherin Alinda Zulfa (2022)
Decreased consciousness is a condition in when a person is not fully aware so that he is unable to respond to a stimulus. Decreased consciousness is one of the indications of patients being treated in the Intensive Care Unit (ICU). Decreased consciousness experienced by ICU patients can be caused by hemodynamic instability. One of the therapies that can be used to treat hemodynamic instability is Holy Quran Recitation (HQR). The purpose of this study was to determine the effectiveness of Holy Quran Recitation (HQR) therapy on vital signs and consciousness of patients with decreased consciousness. The number of respondents involved in this study amounted to two people with one person being given the intervention while the other one was not given the intervention. Measurement of data using the results of vital signs (blood pressure, mean arterial pressure, pulse rate, respiratory rate, and SpO2) and Glasgow Coma Scale (GCS) value. The results of the study after being given Holy Quran Recitation (HQR), found that there were significant differences in vital signs and consciousness between patients who was given the intervention and who was not. Holy Quran Recitation (HQR) therapy is effective in treating hemodynamics, especially vital signs and patient awareness, so it is recommended to be carried out together with pharmacological therapy in the ICU.